Genotypes Diversity and Virulence Factor screening of Trichomonas vaginalis Isolated from Pregnant Women in Mosul (North of Iraq) (Baghdad Science Journal, 2022)
Trichomonas vaginalis is a causative agent of trichomoniasis , one of the most common non-viral sexually transmitted disease (STD) over all the world, especially in immunocompromised women such as pregnant. Wet smear and Giemsa stain are the current methods used in hospital to diagnosis trichomoniasis. DNA based diagnosis is still to be validated to diagnose the local isolates, the objective of the present study was to compare the conventional methods of disease diagnosis with the DNA-based method to diagnose Trichomonas incidence in local isolates. In the present study, 105 samples were collected from outpatient women (18-45 years) of Maternity hospital in Mosul who showed a classical presentation of Trichomonas infection including foul-smelling vaginal discharge with a pH exceeding 4.5. Samples underwent microscopic examination and nucleic acid detection of AP65-1 gene, the wet smear test showed that 16.18%  of the collected specimen were positive while the parasite appeared only in 8.9% of the samples stained with Giemsa dye, the molecular screening for AP65-1gene that encodes for the surface attachment protein showed high sensitivity level of 100 at 50 specificity level in compare with other routine methods, the algorithm was evaluated according to specificity, sensitivity, and predictive values. Random Amplification Polymorphic DNA (RAPD) was achieved to estimate genetic indices among isolated strains. Phylogenetic analysis was performed using PAST (Paleontological statistics software) and dendrogram with neighboring clusters was constructed. According to the outcomes of research, we recommended to utilize a probiotic vaccines and molecular silencing vaccine (like miRNA sense and antisense oligonucleotides) as a treatment in.